Web Database Application with PHP and MySQL, 2nd Edition - Lane, David (O'Reilly, 2011)
This new edition has been redesigned around the rich offerings of PEAR. Several of these, including the Template package and the database-independent query API, are fully integrated into examples and thoroughly described in the text. In addition, through a complex sample application--Hugh and Dave's Wine Store--all the important techniques of dynamic content are introduced. Good design is emphasized, such as dividing logic from presentation. The book introduces PHP 5 and MySQL 4.1 features, while providing techniques that can be used on older versions of the software that are still in widespread use.